Pengaruh Kompetensi Aparatur Dan Sistem Akuntansi Keuangan Terhadap Akuntabilitas Pengelolaan Dana Desa Dimoderasi Sistem Pengendalian Internal - Lisa Firanti Agustini; Ayu Lucy Larassaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the influence of apparatus competency and financial accounting systems on accountability in managing village funds with the internal control system as a moderating variable. This research uses quantitative and qualitative methods. The research sample was taken using a purposive sampling technique with the criteria of village officials related to village fund management in Tulangan District, Sidoarjo Regency. Data were analyzed and tested using WarpPLS 7.0. The results of this research show that apparatus competency has an influence on achieving accountability in village fund management, the internal control system is able to moderate the relationship between apparatus competency and accountability in village fund management. Apart from that, the financial accounting system has an influence on creating accountability in managing village funds, and the internal control system is able to moderate the relationship between the financial accounting system and accountability in managing village funds. This shows that accountability in managing village funds can be achieved if the village government implements an appropriate financial accounting system and is accompanied by the implementation of an internal control system that complies with regulations. Keywords: Apparatus Competence, Financial Accounting System, Internal Control System, Village Fund Management Accountability